Software and Hardware Complex for Setting of Automatic Excitation Regulators of Turbogenerators - Sulaymanova V. A. Venera Almazovna; Borovikov Y. S. Yuri Sergeevich; Andreev M. V. Mikhail Vladimirovich; Suvorov A. A. Aleksey Aleksandrovich (2017, 2017)
Title screen